Direct anterior approach for femoral component revision: Surgical technique for extended trochanteric osteotomy and anterior cortical window - Morcos, Mina W. (J Orthop, 2020)
OBJECTIVE: Direct anterior approach (DAA) is becoming a popular option for both primary and revision total hip arthroplasty (THA). Adequate exposure is crucial in the setting of revision THA. The purpose of this article is to describe two different techniques for expanded femoral exposure through the DAA, the anterior extended trochanteric osteotomy and anterior cortical window. METHODS: Extensile exposure were carried out in cadavers, using the contralateral hip as a control. The exposure and technical viability were assessed. RESULTS: It was demonstrated that both extensile techniques can be carried out safely. CONCLUSIONS: Extensile exposures including femoral osteotomies can be safely carried out for revision THA via DAA.